Stress induced cognitive deficit is differentially modulated in BALB/c and C57Bl/6 mice. Correlation with Th1/Th2 balance after stress exposure - Palumbo, María Laura (2010)
Stress and balance of Th1/Th2 immunity has been implicated in psychiatric disorders. In addition, two genetically different inbred strains of mice, C57BL/6 and BALB/c, which have different balance of Th1/Th2 immunity show distinct behavioral responses, neurodevelopment and neurochemistry parameters. Here, we perform a comparative study on chronic mild stress (CMS) effects upon learning and memory and immunity in both strains. Stressed BALB/c, but not C57Bl/6 mice, showed a poor learning performance in both open field and Y-maze. Also, CMS induced a decrease in number of neurons and thickness on hippocampus of BALB/c mice, but not produces morphological changes in C57BL/6 hippocampus. Oxidative stress, evaluated by reactive oxygen species (ROS) production was increased in hippocampus of CMS-exposed BALB/c but not in stressed C57BL/6. Concerning to immune system, stressed BALB/c mice showed a diminished mitogeninduced T cell proliferation and an increase of B cell proliferation. Moreover, lymphocytes from CMSexposed BALB/c mice showed an increased Th2-type cytokines production (IL-4 and IL-10). On the contrary, lymphocytes from CMS-exposed C57BL/6 mice had an increase in T cell proliferation without changes in B cell proliferation. Also, these lymphocytes showed a higher Th1-type cytokine release (INF- and IL-2). These results suggest a differential effect of stress, being BALB/c more vulnerable to cognitive deficit  associated to stress exposition than C57BL/6 mice. This effect could be related to a differential regulation of Th1/ Th2 cytokine balance, suggesting a better learning performance in individuals that produce Th1 type cytokine after stress exposition.